Implementation of a Decision Support System with a Simple Additive Weighting Method for the Selection of Quality Bird Breeder - Septianto, Naafi; Aryanto, Joko (Advance Sustainable Science, Engineering and Technology, 2024)
Indonesia is a country blessed with abundant natural resources, one of which is the diverse variety of chirping birds that captivate the attention of many. The high demand for these birds has led to a decline in the population of wild chirping birds due to increased illegal capture. To address this issue, bird breeding programs have been implemented. The selection of superior quality chirping birds will determine the offspring produced. Superior quality bird brooders can also increase the selling price of the resulting chicks. Therefore, the determination of superiorquality bird breeders is very crucial for decision makers who are related in this case are chirping bird breeders. If it is not done properly and accurately, the wrong selection of chirping birds often results in various problems. Some of the problems that arise include the results of tillers that have low quality to the difficulty of selling livestock produced tillers. Decision-making models can be used to help chirping bird breeders make decisions. The Simple Additive weighting (SAW) method is expected to be able to help overcome the problems encountered. The purpose of this study was to create a decision-making system for the selection of superior quality chirping birds. It is hoped that there will be no mistakes in the selection of chirping birds.